Emission Characteristics of PCDD/Fs, Heavy Metals, and Nuclides during Incineration of Waste Resins Containing Nuclides - Yuhan Feng; Yingzhe Du; Shiying Li; Lili Li; Shi Feng; Kunfeng Li; Mingxiu Zhan; Jinqing Wang; Xu Xu; Peng Lin (Aerosol and Air Quality Research)
Abstract The waste resins generated from nuclear power plants contain radioactive substances, such as 137Cs and 60Co. The treatment of nuclear power plant waste resins is more challenging compared to conventional resins. In this study, the migration and emission characteristics of heavy metals, PCDD/Fs, and nuclides were investigated in relation to the incineration temperature and addition ratio of waste liquid. The results of tube furnace incineration experiments showed that when the resin was incinerated at 900°C, the PCDD/F concentration in the flue gas was 3.02 ng m−3 (0.31 ng l-TEQ m−3), dominant by polychlorinated dibenzofurans (PCDFs). Furthermore, the low nuclide concentration was observed in the flue gas. Almost no solid residue was generated due to sufficient incineration in the tubular furnace. In the pilot scale experiment, when the resin was incinerated at 900°C, the PCDD/F concentration in the flue gas was 16.97 ng m−3 (0.8 ng I-TEQ m−3). In addition, the majority of the nuclides were solidified in the solid residue produced during incineration, and only trace amounts presented in the solid residue. The total amount of nuclide in the flue gas was 49.5 mg m−3, while it reached 33.269 g kg−1 in the solid residue. This accounted for approximately 76.14% of the initial nuclide content of 218.46 mg kg−1 in the reactant. This study verifies that during the thermal disposal process, most of nuclides and heavy metals in the waste resin will migrate to the solid residue.